(untitled) (Research, Society and Development, 2021)
Introduction: Staphylococcus aureus bacteria is the etiological agent with the highest incidence in skin infections, including infectious cellulitis. Its treatment is contained by antibiotics, but the use of medicinal plants has been used for treatment. Acmella oleracea is a plant of the Asteraceae family known as jambu. Objectives: To evaluate the action of Acmella oleracea leaf extract in co-cultivation of the L929 cell line and Staphylococcus aureus bacteria, simulating the process of infectious cellulitis. Methodology: The MTT and Crystal Violet test was first performed on the L929 cell line, incubated with jambu extract, at concentrations of 500 µg/mL, 1000 µg/mL and 2000 µg/mL. Tests were carried out with Staphylococcus aureus incubated for a period of 24 hours with jambu extract at the same concentrations. Results: In the evaluation of L929 cells in the MTT test, there was a significance in the concentration of 1000 µg/mL showing a low metabolic activity compared to other concentrations. In the crystal violet test there was a greater stimulus in the other concentrations when compared to the control. In bacterial viability, a significant drop in viability was observed when compared to the control. The concentration of 500 µg/mL showed the lowest CFU index. When performing the L929 - S. aureus co-cultivation test after incubation for 24 hours with different concentrations of the extract, it was possible to assess that the action of the extract presented a significant reduction in bacterial viability and did not interfere with the viability of L929 cells. Conclusion: With these results we demonstrate that the Acmella oleracea extract presented an antimicrobial activity without interfering with the L929 fibroblast lineage, thus being able to be used against infectious cellulitis.